Hubungan Antara Citra Diri dengan Kepercayaan Diri pada Remaja Perempuan di Kabupaten Badung - Ni Komang, Pidriyanti; Retnoningtias, Diah Widiawati; Huwae, Gretty Henofela (JURNAL PSIKOLOGI MANDALA, 2025)
The purpose of this study was to determine the relationship between self-image and self-confidence in adolescent girls in Badung Regency, Bali. This study applied a quantitative correlational approach with a sample of 386 adolescent girls in Badung Regency, Bali, who were selected through random sampling. The instruments for measuring self-image and self-confidence have undergone validity and reliability tests, resulting in very high reliability coefficients (0.981 for self-image and 0.979 for self- confidence), making them suitable for use in this study. Based on the results of the hypothesis test, the hypothesis was accepted because the p-value was < 0.001, confirming the existence of a relationship between self-image and self-confidence. The correlation value (r = 0.612) indicates a strong positive relationship, where an increase in self-image is directly proportional to an increase in self-confidence among adolescent girls. This study shows a strong positive relationship between self-image and self-confidence among adolescent girls in Badung Regency, indicating that the better the self-image, the higher the self-confidence.